Symptomatic COVID-19 Reinfection with Pericardial and Pleural Involvement: Case Report - Koyuncu Sokmen, Bedriye; Tugce Hurkal (Journal of the Pakistan Medical Association, 2022)
Coronavirus disease 2019 (COVID-19) is a contagious acute respiratory tract infection caused by Severe Acute Respiratory Syndrome CoronaVirus-2 (SARS-CoV-2), a beta coronavirus first discovered in Wuhan, China in late 2019. COVID-19 is spreading rapidly globally and has been officially declared a pandemic by the World Health Organization (WHO) as of March 2020. Most recent studies suggest that immunity can develop after an episode of severe acute respiratory syndrome Infections. There are few cases with severe symptomatic reinfection. Here we present a case of a healthy 46-year-old man with pericardial-pleural and lung involvement in the setting of COVID-19 infection first, and severe symptomatic reinfection thereafter. Key Words: COVID-19 reinfection, COVID-19 pneumonia, lung CT. Continuous...